Imaging Inflammation – From Whole Body Imaging to Cellular Resolution - Peñate Medina, Tuula; Kolb, Jan Philip; Hüttmann, Gereon; Huber, Robert; Peñate Medina, Oula; Ha, Linh; Ulloa, Patricia; Larsen, Naomi; Ferrari, Arianna; Rafecas, Magdalena; Ellrichmann, Mark; Pravdivtseva, Mariya S.; et al. (Frontiers in Immunology, 2021)
Imaging techniques have evolved lately, allowing whole new concepts, like multimodal imaging, personal medicine, theranostic therapies, and molecular imaging, to increase general awareness. Here we have collected the essential (3D) imaging modalities and evaluated the recent findings on preclinical and clinical inflammation imaging. The focus has been on the feasibility of imaging to aid in inflammation precision medicine, and the key challenges and opportunities of the imaging modalities are presented. Some examples of the current usage in clinics/close to clinics have been brought out as an example. This review evaluates the future prospects of the imaging technologies for clinical application in precision medicine from the pre-clinical development point of view.